KLASIFIKASI PENDIDIKAN DALAM SUDUT PANDANG HADIS NABI - RAHMATULLAH RUSLI (Jurnal Pendidikan Islam, 2017)
Nowadays educating children is not an easy matter. Parents should spare their time while they have no time because they have to make more money to fulfill their daily needs. Open information era such as social media create new problem to parents who don’t have time to educate their children. In Islam we do not need any excessive programs since Islam has taught parents how to educate their children to become good children. So this journal tries to explain an educational program extracted from’Hadiths Sohih.’ Islam explains that education can not be separated from human aspects. These aspects, Physical, Religiousity and Intellectual, should be developed connectedly. They are the objectives of Islamic Development Education which include Moral Teachings, Phisical Education, Intellectual Development, Sex and Social Education.